Tuning StackPhim Ligands: Applications in Enantioselective Borylation and Alkynylation - Dahiya, Gaurav; Abboud, Khalil A.; Aponick, Aaron (Synthesis, 2022)
Here we present a new stack ligand with a modified imidazoline backbone prepared from cyclohexanediamine. This new stack ligand, Cy-StackPhim, has been found to complement the parent StackPhim ligand in an enantioselective borylation reaction. Additionally, a correlation between the nature of substituents on the imidazoline ring and the substituents on the electrophile is also discussed.
Keywords: axial chirality; stack ligands; P,N-ligands; ligand tuning; borylation; alkynylation; A3-coupling; ligand synthesis